Merging genotypes: graft union formation and scion–rootstock interactions - Gautier, Antoine T.; Chambaud, Clément; Brocard, Lysiane; Ollat, Nathalie; Gambetta, Gregory A.; Delrot, Serge; Cookson, Sarah J. (Journal of experimental botany, 2019)
Grafting has been utilised for at least the past 7000 years. Historically, grafting has been developed by growers without particular interest beyond the agronomical and ornamental effects, and thus knowledge about grafting has remained largely empirical. Much of the commercial production of fruit, and increasingly vegetables, relies upon grafting with rootstocks to provide resistance to soil-borne pathogens and abiotic stresses as well as to influence scion growth and performance. Although there is considerable agronomic knowledge about the use and selection of rootstocks for many species, we know little of the molecular mechanisms underlying rootstock adaptation to different soil environments and rootstock-conferred modifications of scion phenotypes. Furthermore, the processes involved in the formation of the graft union and graft compatibility are poorly understood despite over a hundred years of scientific study. In this paper, we provide an overview of what is known about grafting and the mechanisms underlying rootstock–scion interactions. We highlight recent studies that have advanced our understanding of graft union formation and outline subjects that require further development.